Optimisation of cricket pitch rolling - Shipton, Peter (Cranfield University, 2008)
In the game of cricket, where a ball is bounced on a natural clay soil pitch between the ‘bowler’ and ‘batsman’, the ball-surface interaction is critical and is one of the most important factors responsible for the quality of play. Rolling of the playing surface with a smooth-wheel roller is common practice and this is intended to encourage pace, but with a predictable ball bounce that will provide a fair and safe playing surface. Current rolling management is largely based on anecdotal evidence and little work has previously being carried out in the UK to quantify the effects of rolling on cricket soils or to determine optimum rolling practice. Initiatives by the England and Wales Cricket Board (the project sponsors) to advance the commercial viability of the game of cricket and to increase player participation provide commercial justification for this project. This thesis aims to improve the fundamental understanding of the scientific principles of pitch preparation and to develop practical guidelines on roller use to help cricket groundsmen produce playing surfaces with the desired playability characteristics. A diverse methodology was used to meet the project objectives. A survey of current practice was conducted to inform experimental design and inform the targeting of rolling guidelines. Dynamic and static triaxial experiments were combined with standard laboratory tests to establish soil mechanical parameters for cricket soils. Field experimental plots and a project designed rolling simulator were used to investigate the interaction between soil mechanical and roller physical properties and to establish rolling management protocols. A grass rooting experiment was also conducted to determine the effect of soil density on root growth and distribution within the compacted soil profile. The survey of current practice established a wide range in rolling practice, particularly in the time allocated to rolling in the spring and for summer pre-match rolling. The experimental results developed the relationship between moisture and soil mechanical properties of cricket soils indicating an increase in plastic and elastic strain with an increase in moisture in un-saturated soils. An increase in soil moisture from 16% to 25% gravimetric moisture content was also shown to increase horizontal movement under a towed roller; however the inclusion of grass roots into the soil profile considerably reduced soil displacement. Soil optimum moisture conditions were identified for a range of roller specifications; 24% gravimetric moisture for a 750 kg m -3 roller and 22% for a 920 kg m -3 roller. Roller speed (0.7 km h -1 ) and the amount of roller passes required (four passes of a two drum roller in the spring and a total of 10 passes for summer match preparation) were established for cricket pitch preparation. Results also indicated a significant potential to reduce annual rolling times when undertaken in optimum soil moisture conditions. This could result in a substantial reduction in cost to the cricket industry and a reduction in CO2 emissions.